2018
DOI: 10.1177/0954409718777371
|View full text |Cite
|
Sign up to set email alerts
|

Energy absorption design study of subway vehicles based on a scaled equivalent model test

Abstract: To obtain the characteristics of collision energy absorption and improve the passive safety of subway vehicles, the energy absorption design of subway vehicles was studied based on a one-seventh-scale model crash test. A full-size three-dimensional model of a subway vehicle was established using the multibody dynamics software MADYMO. The simulation results of the dynamics model were scaled down according to the similarity coefficients. By comparing the simulation results with the scaled model test results, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The numerical simulations exhibited the similar relationships among deformation, acceleration, and energy absorption in full-scale and scaled models. Based on a one-seventh-scaled model crash test, Xu et al 24 studied the energy absorption design of subway vehicles. The results indicated that the collision dynamics model of subway vehicles is relatively accurate.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulations exhibited the similar relationships among deformation, acceleration, and energy absorption in full-scale and scaled models. Based on a one-seventh-scaled model crash test, Xu et al 24 studied the energy absorption design of subway vehicles. The results indicated that the collision dynamics model of subway vehicles is relatively accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the theory of train collision dynamics, the known vehicle weights, marshaling, and other basic information, a longitudinal train collision dynamics program is developed, a series of numerical simulation calculations are conducted for collision energy allocation schemes, and the maximum mean acceleration of each vehicle and its energy absorption rate during the collision are obtained. e optimal energy allocation plan is determined based on the calculation results [15][16][17]. is process requires many numerical simulation calculations and consumes considerable computational time, resulting in low predesign efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…e relationships between the energy absorption of each interface and the initial collision kinetic energy of the train, the number of train formations, and the crushing platform force of the energy-absorbing structure are studied. e relationship between the energy absorption capacity of the collision interface and each parameter is determined to provide the initial value of the energy allocation scheme [15,[28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that the energy generated by a rail vehicle collision is extremely large; because the head car is located at the first impact interface, it has a higher demand than the other rail cars in terms of the energy-absorbing capability of the energy-absorbing device. 3538 However, to reduce the aerodynamic drag, the cross-sectional area of the high-speed train is limited. A honeycomb energy-absorbing device should be designed in such a way that it is longer than the traditional energy-absorbing devices, which may lead to bending, destruction and uncontrollable deformation of the honeycomb; these factors are not conducive to energy absorption.…”
Section: Introductionmentioning
confidence: 99%